Nomenclature of genetic movement disorders: Recommendations of the international Parkinson and movement disorder society task force. Issue 4 (15th April 2016) - Marras, Connie; Lang, Anthony; van de Warrenburg, Bart P.; Sue, Carolyn M.; Tabrizi, Sarah J.; Bertram, Lars; Mercimek‐Mahmutoglu, Saadet; Ebrahimi‐Fakhari, Darius; Warner, Thomas T.; Durr, Alexandra; Assmann, Birgit; Lohmann, Katja; et al.
ABSTRACT: The system of assigning locus symbols to specify chromosomal regions that are associated with a familial disorder has a number of problems when used as a reference list of genetically determined disorders, including (I) erroneously assigned loci, (II) duplicated loci, (III) missing symbols or loci, (IV) unconfirmed loci and genes, (V) a combination of causative genes and risk factor genes in the same list, and (VI) discordance between phenotype and list assignment. In this article, we report on the recommendations of the International Parkinson and Movement Disorder Society Task Force for Nomenclature of Genetic Movement Disorders and present a system for naming genetically determined movement disorders that addresses these problems. We demonstrate how the system would be applied to currently known genetically determined parkinsonism, dystonia, dominantly inherited ataxia, spastic paraparesis, chorea, paroxysmal movement disorders, neurodegeneration with brain iron accumulation, and primary familial brain calcifications. This system provides a resource for clinicians and researchers that, unlike the previous system, can be considered an accurate and criterion‐based list of confirmed genetically determined movement disorders at the time it was last updated. © 2016 International Parkinson and Movement Disorder Society